Evaluation the Nutritional Effect of Lavandula angustifolia L. Essential Oil on Normal and High Blood Pressure and Changes of the Aorta in the Rat - S Momen Abadi; HR Sameni; M Zahedi Khorasani; A Vakili (Institue of Medicinal Plants, ACECR, 2015)
Background: Hypertension is a health problem and alternative medicine is offered for its controlling. Objective: Nutritional effects of Lavandula angustifolia L. (lavender) oil on high blood pressure (BP), and histological changes of the aorta in rat has been investigated in this study. Methods: Therty five male wistar rats were divided into 5 groups; normal, hypertensive and control. Hypertension was induced by daily L-NAME administration in drinking water for 6 weeks and lavender oil (500 mg/kg) or its vehicle was given orally simultaneously. After basal BP measurement, lavender (50 mg/kg, iv) was injected in control groups. Histological evaluation of the thoracic aorta included staining with hematoxylin-eosin and orcein methods. Results: Hypertension induction increased mean arterial BP from 106 to 177 mm Hg and lavender treatment reduced it to 140 mm Hg (P< 0.001). Lavender had no effect on normal rats. Intravenous injection of lavender reduced BP about 75% in normotensive and hypertensive rats (P<0.001). Hypertension induction increased cross-section area, aorta and media thickness, and reduced elastic lamina thickness (P<0.001). Lavender treatment reduced cross-section area of the aorta and media thickness, and increased elastic lamina thickness (P < 0.05). Hypertension and treatment had no effect on advanthia and elastic lamina numbers. Conclusion: Nutritional lavender oil prevented BP increases and pathological changes of the aorta in hypertensive rats. It seems lavender oil is beneficial for prophylaxis of hypertension.